A clinical case of COVID-19 in a patient with Hodgkin lymphoma and brain damage - G. K. Zoloev; A. A. Kosovskikh; O. V. Rudenkova; Zh. V. Pikelgaupt; V. V. Manzhos; K. V. Cherevatenko (Фундаментальная и клиническая медицина)
Severe COVID-19 is not restricted to the lungs but also affects other organs and tissues, making the choice of the therapeutic regimen challenging, in particular with patients having comorbid conditions. Here we present the case of successful treatment of COVID-19 in patient with Hodgkin lymphoma and brain injury, focusing on the signs, symptoms, and differential diagnosis.